The Effect of Leadership Style, Work Culture, and Teamwork on Financial Performance at PT. Bpr Supra Artapersada Ciranjang Cianjur Branch Office for the Period 2022-2024 - Aam Aminudin; Ucu Supriatna (Publikasi Indonesia, 2026)
Background: The development of the microbanking industry in Indonesia has encouraged BPR (Bank Perekonomi Rakyat) to increase its competitiveness and financial resilience. Healthy financial performance at the branch office level is a reflection of management effectiveness, quality of human resources, and synergy between employees in carrying out operations. Objective: This study aims to analyze the influence of leadership style, work culture, and teamwork on financial performance at PT. BPR Supra Artapersada, Ciranjang Branch, Cianjur, during 2022–2024. The research phenomenon is based on the variation in financial performance across periods, which may be affected by internal organizational factors such as leadership behavior, work culture, and team collaboration. Methods: This research uses a quantitative associative approach, combining primary data from questionnaires distributed to 30 employees and secondary data from OJK APOLO published financial reports from 2022–2024. The data were analyzed using multiple linear regression with SPSS version 25.0. Results: The results show that: (1) Leadership style has a positive and significant effect on financial performance; (2) Work culture has a positive and significant effect on financial performance; (3) Teamwork has a positive and significant effect on financial performance; and (4) All variables simultaneously affect financial performance, with an R² value of 0.742. Conclusion: Teamwork has the most dominant influence on financial performance. These findings indicate that organizational behavior factors play an important role in improving operational efficiency and profitability of BPR branches.